2017
DOI: 10.1039/c6lc01574c
|View full text |Cite
|
Sign up to set email alerts
|

Multi-chamber microfluidic platform for high-precision skin permeation testing

Abstract: The established in vitro tool used for testing the absorption and penetration of chemicals through skin in pharmacology, toxicology and cosmetic science is the static Franz diffusion cell. While widespread, Franz cells are relatively costly, low-throughput and results may suffer from poor reproducibility. Microfluidics has the potential to overcome these drawbacks. In this paper, we present a novel microfluidic skin permeation platform and validate it rigorously against the Franz cell by comparing the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…This gut-on-a-chip device, along with other intestinal chips such as HuMiX, has been used to recapitulate the interplay between intestinal microbes and the epithelium (Kim et al, 2015; Shah et al, 2016). Innovative perfusable vascularized skin-on-a-chip models (Wufuer et al, 2016; Mori et al, 2017) or immune-competent models (Ramadan and Ting, 2016) have been proposed, both aiming to create more physiologically relevant skin equivalents for drug screening and disease modeling (Abaci et al, 2015; Alberti et al, 2017; van den Broek et al, 2017; Sriram et al, 2018).…”
Section: Lab-on-a-chip Devices Mimicking Epithelial Tissuesmentioning
confidence: 99%
“…This gut-on-a-chip device, along with other intestinal chips such as HuMiX, has been used to recapitulate the interplay between intestinal microbes and the epithelium (Kim et al, 2015; Shah et al, 2016). Innovative perfusable vascularized skin-on-a-chip models (Wufuer et al, 2016; Mori et al, 2017) or immune-competent models (Ramadan and Ting, 2016) have been proposed, both aiming to create more physiologically relevant skin equivalents for drug screening and disease modeling (Abaci et al, 2015; Alberti et al, 2017; van den Broek et al, 2017; Sriram et al, 2018).…”
Section: Lab-on-a-chip Devices Mimicking Epithelial Tissuesmentioning
confidence: 99%
“…Liu et al for instance looked at the clearance rates of testosterone in a coculture of hepatocytes on electrospun fibers . Alberti et al meanwhile studied the penetration of testosterone through organotypic skin . Using explant cultures of rodent and human adipose tissue, further in vitro studies demonstrated the reduction of proinflammatory cytokines due to estrogen as well as sex differences in both spontaneous and estrogen‐stimulated leptin secretion …”
Section: Sex‐differences In Nonfemale‐specific Organ‐on‐a‐chip Systemsmentioning
confidence: 99%
“…Skin-on-chip devices offer innovative and state-of-the-art platforms essential to overcome the above-mentioned limitations of Franz diffusion cells [10]. In some studies, organotypic cultures are cultivated in the chips to mimic human skin and the transepithelial electrical resistance (TEER) is detected [11,12,13] for characterization the diffusion properties. The tissue vascularization can also be considered in the preparation of skin cell containing co-cultures [14].…”
Section: Introductionmentioning
confidence: 99%